2021
DOI: 10.1089/neu.2021.0116
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Outcome Differences between Men and Women following Mild Traumatic Brain Injury

Abstract: Research on soft artificial muscles (SAMs) is rapidly growing, both in developing new actuation ideas and improving existing structures with multifunctionality. The human body has more than 600 muscles that drive organs and joints to achieve desired functions. Inspired by the human muscles, this article presents a new type of SAM fiber formed from twisting and braiding soft hydraulic filament artificial muscles with high aspect ratio, high strain, and high energy efficiency. We systematically investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…In a recent retrospective study of mild traumatic brain injury (TBI), females had a worse outcome than males 3, 4 . These sex related differences in outcome are not explained by sociodemographic or care pathways, and have yet to be identified 3, 5, 6 . Clinically relevant animal models of TBI can provide insight into the mechanisms that underlie the brain response to injury, factors contributing to pathological outcomes, and facilitate screening of therapeutics to improve functional recovery.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent retrospective study of mild traumatic brain injury (TBI), females had a worse outcome than males 3, 4 . These sex related differences in outcome are not explained by sociodemographic or care pathways, and have yet to be identified 3, 5, 6 . Clinically relevant animal models of TBI can provide insight into the mechanisms that underlie the brain response to injury, factors contributing to pathological outcomes, and facilitate screening of therapeutics to improve functional recovery.…”
Section: Introductionmentioning
confidence: 96%
“…The worse outcome could not be explained by sociodemographic or care pathways, and have yet to be identified 3,5,6 . Animal models of TBI can provide insight into the mechanisms that underlie the brain response to injury, factors contributing to pathological outcomes, and facilitate screening of therapeutics to improve functional recovery.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Complex experiences of repetitive mild TBI with environmental and/or emotional stressors are particularly relevant to military service members, who may experience events of head impact and/or acceleration, blast exposure, and stress due to traumatic experiences, adverse conditions and sleep deficiency. Natural history studies in military and civilian patients with TBI will continue to be important for understanding the heterogeneity of events, including stress and blast exposures, and patient factors such as age and sex/gender that influence symptom expression [2, 7, 8]. To complement these clinical studies in understanding factors contributing to TBI outcomes, specific components of the stress and mild TBI events can be modeled in animals.…”
Section: Introductionmentioning
confidence: 99%
“…The study design is for each component (environmental stressors, repetitive blast and mild brain injury, or isolation stress) to be mild so as not to independently produce significant symptoms but rather to result in persistent symptom expression when experienced in combination over a prolonged period of time. In studies of mild TBI, significant differences have been observed in outcomes between men and women [7, 8]. Therefore, sex was evaluated for the response to stress and head injury exposures.…”
Section: Introductionmentioning
confidence: 99%